Visiting Sacred Sites as Seeking an Alternative Healing Method During the COVID-19 Pandemic: The Example of Joshua's Tomb - Harmanci, Meric; Aydin, Hilal Otyakmaz (Rector CIU Cyprus Int Univ, 2023)
This study aims to investigate the reasons why people visit tombs of people believed to have a religious identity, and to determine the relationship between these visits and sickness in general and COVID-19 in particular. For this study, Joshua's Tomb located in Istanbul was selected. The study was designed in phenomenology. The study group consisted of twenty two visitors who visited Joshua's Tomb between May 26, 2021 and June 04, 2021. Within the scope of ethnological field research, data of the study were collected by directed interviews and natural observation. As a result of content analysis, four themes emerged at the end of the study: reasons for vising Joshua's Tomb, seeking healing at Joshua's Tomb, people visiting Joshua's Tomb during the COVID-19 pandemic and visitors seeking healing during the COVID-19 pandemic. Joshua's Tomb draws attention as one of the sacred places and spiritual areas that people turn to for various reasons, especially with the expectation of healing, during the period when the epidemic was intense and people did not prefer to leave their homes, except for essential reasons.
Keywords: Joshua; tomb; beliefs; healing; COVID-19; Arts & Humanities - Other Topics; Literature